An Infrared Emitter Driver Circuit of SAT for MILES Application - Siradjuddin, Indrazno; Wahyu Aulia Nurwicaksana; Septyana Riskitasari; Gillang Al Azhar; Arief Rahman Hidayat; Rendi Pambudi Wicaksono (Journal of Evrímata: Engineering and Physics, 2024)
This paper presents the design and simulation of an infrared emitter driver circuit for the MILES (Multiple Integrated Laser Engagement System) application. The circuit aims to efficiently drive a high-power IR emitter, maximizing output power while maintaining compatibility with low-power embedded systems (e.g., ESP32). Key design considerations include the selection of an appropriate IR diode emitter, driver circuit topology (utilizing a push-pull amplifier and low-side MOSFET driver for fast switching), pulse shaping techniques to optimize rise and fall times, and thermal management strategies. Simulation results demonstrate the effectiveness of the proposed design in achieving high power output (4.5W) with fast switching speeds and minimal ringing, suitable for MILES applications requiring precise and rapid IR LED control.